Kebenaran Informasi Di Media Sosial: Tinjauan Kritis Ilmu Komunikasi - Chrisjon Situmorang; Nina Yuliana (Jurnal Ilmu Komunikasi Balayudha, 2026)
The way people create, distribute, and access information has changed completely as a result of the development of social media technology. There are significant obstacles related to the credibility and accuracy of information provided by these platforms, even though they are quick and easy to use. The spread of deliberately falsified information, fake news, and unverified content has become a significant problem that affects public trust, decision-making processes, and collective understanding. From a communication science perspective, this study attempts to comprehensively examine the concept of truth in social media. A qualitative approach was applied in this research. This is done through a peer-reviewed literature review of academic books and journal articles published in the last five years. The main findings show that the development of information truth on social media is greatly influenced by the impact of algorithms, the decline of the role of conventional filtering, and active user participation. As a result, maintaining the truth and accuracy of information in the digital age requires increased critical awareness and communication literacy.